2019
DOI: 10.1080/0022250x.2019.1664508
|View full text |Cite
|
Sign up to set email alerts
|

Relative deprivation as a cause of risky behaviors

Abstract: Combining a standard measure of concern about low relative wealth and a standard measure of relative risk aversion leads to a novel explanation of variation in risk-taking behavior identified and documented by social psychologists and economists. We obtain two results: (1) Holding individual i's wealth and his rank in the wealth distribution constant, the individual's relative risk aversion decreases when he becomes more relatively deprived as a result of an increase in the average wealth of the individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This strand of literature hence suggests that migration decisions are influenced by risk-taking attitudes. Meanwhile, Stark (2020) shows that RD could affect individuals' relative risk-aversion preferences. Put altogether, RD would have a direct and an indirect relation with migration decisions, the latter through altering individual's tolerance to risk.…”
Section: Data and Resultsmentioning
confidence: 99%
“…This strand of literature hence suggests that migration decisions are influenced by risk-taking attitudes. Meanwhile, Stark (2020) shows that RD could affect individuals' relative risk-aversion preferences. Put altogether, RD would have a direct and an indirect relation with migration decisions, the latter through altering individual's tolerance to risk.…”
Section: Data and Resultsmentioning
confidence: 99%
“…That is tough. (Hector,rural area,43) Economic research has indeed shown that relative deprivation is linked to risky behaviours, such as gambling (Stark, 2020), and that poverty can lead to increased engagement in criminal activities (Kawachi et al, 1999). However, it is important to consider why individuals from lower socio-economic backgrounds might be more inclined to gamble or commit crimes rather than pursue migration.…”
Section: Perceptions and Realities: The Risks And Motivations Of Lowe...mentioning
confidence: 99%
“…In particular, in Stark (2020) the interest was in identifying the attitude of people towards risk taking under the assumption that risk-taking behavior is conditioned by social preferences. To account for this, relative wealth was incorporated as a variable: a person's own wealth matters, but so does a comparison of a person's wealth to the wealth of others who are positioned higher up in the wealth distribution.…”
Section: Introductionmentioning
confidence: 99%